2011
DOI: 10.1186/1471-2431-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Age specific aetiological agents of diarrhoea in hospitalized children aged less than five years in Dar es Salaam, Tanzania

Abstract: BackgroundThis study aimed to determine the age-specific aetiologic agents of diarrhoea in children aged less than five years. The study also assessed the efficacy of the empiric treatment of childhood diarrhoea using Integrated Management of Childhood Illness (IMCI) guidelines.MethodsThis study included 280 children aged less than 5 years, admitted with diarrhoea to any of the four major hospitals in Dar es Salaam. Bacterial pathogens were identified using conventional methods. Enzyme Linked Immunosorbent Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
61
5
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 16 publications
30
61
5
5
Order By: Relevance
“…This might be due to the environmental and personal hygiene factors. The presence of E. coli in most of the samples confirmed this as a common causative agent of bacterial diarrhoea and agreement to earlier reports 21 . Salmonella was the second cause of diarrhoea in our study and contradictory to the earlier reports 22 of who revealed the presence of Shigella spp.…”
Section: Resultssupporting
confidence: 77%
“…This might be due to the environmental and personal hygiene factors. The presence of E. coli in most of the samples confirmed this as a common causative agent of bacterial diarrhoea and agreement to earlier reports 21 . Salmonella was the second cause of diarrhoea in our study and contradictory to the earlier reports 22 of who revealed the presence of Shigella spp.…”
Section: Resultssupporting
confidence: 77%
“…Estos resultados coinciden con reportes previos de estudios en países en desarrollo, según los cuales las tasas de mortalidad y morbilidad infantil por síndrome diarreico agudo comúnmente se asocian a la edad y a la condición social (3,10,(28)(29)(30). Además, estas enfermedades son más frecuentes durante los primeros dos años de vida, lo cual refleja un patrón que combina el declive de los niveles de anticuerpos maternos, la pérdida de inmunidad activa en el infante y la introducción de alimentos potencialmente contaminados con bacterias fecales (1,29).…”
Section: Discussionunclassified
“…La característica epidemiológica más sobresaliente de las infecciones por ECEP es su distribución casi exclusivamente en niños menores de dos años; este patrón se ha asociado a los factores socioepidemiológicos determinantes en este grupo de edad y a su inmadurez inmunológica (10,18,30). Asimismo, se ha sugerido que en los mayores de dos años se pueden aislar cepas ECEP sin que haya una correlación estadística entre dichas cepas y los casos de enfermedad infecciosa (31).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Penyebab diare terkait infeksi banyak ditemukan pada anak di bawah usia 5 tahun. Mikroorganisme penyebab diare tidak selalu bakteri 1,4 . Diare persisten memiliki kecenderungan disebabkan oleh infeksi bakteri.…”
unclassified